A green and simple procedure to synthesize dysprosium cerate plate-like nanostructures and their application in the electrochemical sensing of mesalazine - Zinatloo-Ajabshir, Sahar; Mahmoudi-Moghaddam, Hadi; Amiri, Mahnaz; Akbari Javar, Hamid (Journal of materials science. Materials in electronics, 2024)
This study introduced the synthesizing of plate-like dysprosium cerate (PL-Dy 2 Ce 2 O 7 ) nanoparticles using a simple and fast procedure. The new nanostructure was developed by orange juice as a green capping agent. The synthesized nanoparticles were characterized via scanning electron microscopy (SEM) and other characterization techniques. A modified screen-printed electrode based on PL-Dy 2 Ce 2 O 7 nanocomposite (PL-Dy 2 Ce 2 O 7 /SPE) has been made and utilized for sensitive detection of mesalazine (MEZ). The efficiency for the electrochemical determination of MEZ was assessed via differential pulse voltammetry (DPV) and cyclic voltammetry (CV) in 0.1 M phosphate buffer solution (PBS). The Dy 2 Ce 2 O 7 /SPE as an efficient electrochemical sensor displayed suitable electrocatalytic activity towards the electro-oxidation of MEZ. The results revealed that MEZ oxidation was a typical diffusion-controlled electrochemical oxidation procedure. Under optimal experimental parameters, the developed modified electrode showed a broad linear range of MEZ between 0.02 and 145 µM and the value of 0.008 µM was calculated for the detection limit. In addition, the developed method exhibited an acceptable repeatability and reproducibility with no significant change in response after continuous measurements. In the presence of interfering compounds, a new PL-Dy 2 Ce 2 O 7 modified electrode displayed high selectivity for MEZ detection. Finally, by successfully detecting MEZ in tablet, human blood serum, and urine, the practical application of the sensor was proved.